Design and characterization of a fully compliant out-of-plane thermal actuator - Ogando, K.; La Forgia, N.; Zárate, J.J.; Pastoriza, H. (Elsevier, 2012)
Fil: Ogando, K. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina